2020
DOI: 10.1002/jlb.3vmr0220-438rr
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neutrophil cytoplasmic antibodies (ANCA): Antigen interactions and downstream effects

Abstract: Neutrophils are the most abundant leukocytes in circulation and are key "first responders" in the immune response to infectious and non-infectious stimuli. Unlike other immune cells, neutrophils can mount a robust response (including a change in surface markers and the production of extracellular traps and reactive oxygen species) just minutes after sensing a disturbance. It has been speculated that, in some individuals, the activation of neutrophils inadvertently leads to the generation of anti-neutrophil cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 124 publications
(198 reference statements)
0
6
0
Order By: Relevance
“…ANCAs are reactive against multiple antigens in the cytoplasmic and perinuclear regions in neutrophils and monocytes. The most prevalent ANCAs in ANCA‐associated vasculitis target myeloperoxidase and proteinase 3 and are strongly associated with small vessel vasculitis 28 . It is believed that, in genetically predisposed patients, the first neutrophil immune response may lead to antigen presentation and chronic immune dysregulation in small vessel vasculitis 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANCAs are reactive against multiple antigens in the cytoplasmic and perinuclear regions in neutrophils and monocytes. The most prevalent ANCAs in ANCA‐associated vasculitis target myeloperoxidase and proteinase 3 and are strongly associated with small vessel vasculitis 28 . It is believed that, in genetically predisposed patients, the first neutrophil immune response may lead to antigen presentation and chronic immune dysregulation in small vessel vasculitis 28 .…”
Section: Discussionmentioning
confidence: 99%
“…28 It is believed that, in genetically predisposed patients, the first neutrophil immune response may lead to antigen presentation and chronic immune dysregulation in small vessel vasculitis. 28 However, the immunopathology of vasculitis is still unclear. Several models have suggested that T-lymphocytes may play a leading role in the loss of tolerance and development of autoimmunity.…”
Section: Accepted Articlementioning
confidence: 99%
“…There are only a limited number of studies showing vasculitis associated autoantibodies in COVID-19 patients ( Gazzaruso et al, 2020 ; Sacchi et al, 2020 ; Vlachoyiannopoulos et al, 2020 ; Chang et al, 2021a ). In ANCA associated vasculitis, the most common ANCAs target MPO and PR3 which are closely related with small vessel vasculitis ( Sundqvist et al, 2020 ). Vasculitis associated MPO antibody was detected only in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…Although MPO and PR3 released by neutrophils may associate with the endothelium and in this manner target the endothelium for ANCA-mediated damage, it is also possible that disease processes are the result of the indirect action of ANCA, or are independent of autoantibodies, as may be the case in patients with ANCA-negative vasculitis (2).…”
Section: Introductionmentioning
confidence: 99%